Verification of the Accuracy of Mergers and Acquisitions in Poland in 2012-2020 - Katarzyna SWIETLA; Joanna TOBOREK-MAZUR (Communications of International Proceedings, 2021)
The basic reason for the functioning of enterprises is the maximization of benefits by achieving positive financial results with the minimum possible involvement of the enterprise's capital. The aim of the study is to analyze changes in the structure of capital groups resulting from the processes of mergers and acquisitions. Their value was adopted as the selection key for the analyzed transactions, focusing on the highest volumes. The research period was established for nine consecutive years covering the period from 2012 to 2020. The study contains a classification analysis of mergers and acquisitions and a separate set of key motives underlying them. The article uses research methods such as analysis and criticism of the literature, analysis of financial documents (financial statements of the studied sample), preparation and compilation of data in tables and their presentation in charts, as well as the interpretation of the obtained results, both in comparative and descriptive terms. In this context 35 items containing both review of scientific research by numerous authors and reports and analyzes allowing for practical exemplification of the issue between 2012-2020 were mooted. Not only the synergy effect in the context of undertaken mergers and acquisitions transactions was pointed out, but also other important elements influencing the merger process. The continuity of M&A transactions in Poland in 2012-2020 was verified. Conclusions from undertaken research were presented at the end of this article. The result of the research was the answer to undertaken questions and confirmation of the hypotheses leading to the conclusion that the number of M&A transactions were decreasing over the period considered. Despite this, carried out research confirmed that the largest mergers and acquisitions had survived until the end of the second quarter of 2021, which confirms their economic value.
Keywords: Mergers and acquisitons; effect of synergy; limited growth; multi-level structures.